blaTEM and vanA as indicator genes of antibiotic resistance contamination in a hospital–urban wastewater treatment plant system - Narciso-da-Rocha, Carlos (2015)
Four indicator genes were monitored by quantitative PCR in hospital effluent (HE) and in the raw and treated wastewater of the municipal wastewater treatment plant receiving the hospital discharge. The indicator genes were the class 1 integrase gene intI1, to assess the capacity of bacteria to be involved in horizontal gene transfer processes; blaTEM, one of the most widespread antibiotic resistance genes in the environment, associated with Enterobacteriaceae; vanA, an antibiotic resistance gene uncommon in the environment and frequent in clinical isolates; and marA, part of a locus related to the stress response in Enterobacteriaceae. Variation in the abundance of these genes was analysed as a function of the type of water, and possible correlations with cultivable bacteria, antimicrobial residue concentrations, and bacterial community composition and structure were analysed. HE was confirmed as an important source of blaTEM and vanA genes, and wastewater treatment showed a limited capacity to remove these resistance genes. The genes blaTEM and vanA presented the strongest correlations with culturable bacteria, antimicrobial residues and some bacterial populations, representing interesting candidates as indicator genes to monitor resistance in environmental samples. The intI1 gene was the most abundant in all samples, demonstrating that wastewater bacterial populations hold a high potential for gene acquisition